Guided by humanitarian principles - Vogt, A; Colsell, S (Refugee Studies Centre, University of Oxford, 2014)
Caritas Luxembourg’s work with refugees, IDPs and migrants in Colombia, Lebanon and Luxembourg offers some examples of the ways in which a faith-based organisation may be advantaged or disadvantaged by its faith basis and how it needs to adhere to humanitarian standards